SUCCESSFUL SURGICAL TREATMENT OF SPONTANEOUS RAPTURE OF COMMON HETATIC BILE DUCT, COMPLICATED WITH RETROPERITONEAL BELOMA WITH PERFORATION INTO PERITONEAL CAVITY IN CONDITIONS OF REGIONAL DISTRICT HOSPITAL - Makhmudov, A.Kh.; Elmuradov, R.Kh.; Mukhtarov (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Spontaneous rupture of posterior-lateral wall of common hepatic bile duct. During pre- and intraoperative period have arisen some difficulties in diagnosing cause of generalized biliary peritonitis. As result of surgical treatment patient recovered.